Low radio frequency observations and spectral modelling of the remnant of Supernova 1987A - Callingham, J.; Gaensler, B.; Zanardo, G.; Staveley-Smith, L.; Hancock, P.; Hurley-Walker, N.; Bell, M.; Dwarakanath, K.; Franzen, T.; Hindson, L.; Johnston-Hollitt, M.; Kapinska, A.; et al. (Oxford University Press, 2016)
We present Murchison Widefield Array observations of the supernova remnant (SNR) 1987A between 72 and 230 MHz, representing the lowest frequency observations of the source to date. This large lever arm in frequency space constrains the properties of the circumstellar medium created by the progenitor of SNR 1987A when it was in its red supergiant phase. As of late 2013, the radio spectrum of SNR 1987A between 72 MHz and 8.64 GHz does not show any deviation from a non-thermal power law with a spectral index of -0.74 ± 0.02. This spectral index is consistent with that derived at higher frequencies, beneath 100 GHz, and with a shock in its adiabatic phase. A spectral turnover due to free-free absorption by the circumstellar medium has to occur below 72 MHz, which places upper limits on the optical depth of ≤0.1 at a reference frequency of 72 MHz, emission measure of ~<13 000 cm-6 pc, and an electron density of ~<110 cm-3. This upper limit on the electron density is consistent with the detection of prompt radio emission and models of the X-ray emission from the supernova. The electron density upper limit implies that some hydrodynamic simulations derived a red supergiant mass-loss rate that is too high, or a wind velocity that is too low. The mass-loss rate of ~5 × 10-6 M☉ yr-1 and wind velocity of 10 km s-1 obtained from optical observations are consistent with our upper limits, predicting a current turnover frequency due to free-free absorption between 5 and 60 MHz.